Solar PV integrated hosting capacity analysis with Volt-VAr compensation - Anonas, Samuel David S.
The volume of installed Solar Photovoltaics in the distribution sector is projected to increase in the coming years and it is expected to soon disrupt the radial behavior of Distribution feeders. Given this, the need to determine the maximum threshold for Solar PV installations is of high significance. This study performed an integrated hosting capacity simulation, which takes into account the combined effects of both MV and LV Solar PV installations, on a 34.5/0.24 kV residential Philippine feeder having a daily average of over 200,000 kWh. In conjunction with this, long-duration voltage variations and circuit power factor variations were selected as the performance indices of choice. The results showed that for the residential feeder, the integrated hosting capacity was achieved by deploying Solar PV installations, equivalent to 4.7 MW, at the MV level only. In addition, the integrated hosting capacity methodology was also able to capture other hosting capacities that were lower but comparable to the MV-only result. These hosting capacities were achieved by deploying Solar PVs both at the MV and LV voltage levels. These additional findings provided insights on the flexibility and importance of this integrated approach due to the diverse and practical deployment scenarios that can be explored by the Distribution Utility. One insight is that Solar PVs at the MV level, whether accompanied by installations at the LV level or not, were able to contribute higher amounts of kW when placed near the substation. Furthermore, the results suggested that LV installations needed Voltage support whereas MV installations required VAr support. The deployment scenario producing the hosting capacity was then subjected to mitigation strategies in the form of Volt-VAr compensation to improve and maximize the Solar hosting capacity of the feeder. This resulted to an additional 2.9 MW on the hosting capacity of the feeder. The results of this study can assist Distribution Utilities in planning efficient and practical system improvements ahead of future Solar PV deployments.